ANTIMICROBIAL ACTIVITY OF SPHAGNETICOLA TRILOBATA (L.) PRUSKI, AGAINST SOME HUMAN PATHOGENIC BACTERIA AND FUNGI - TOPPO, KUMUDINI INDIRA; GUPTA, SHUBHA; KARKUN, DEEPAK; AGRWAL, SHIRISH; KUMAR, ANIL (The Bioscan, 2013)
The side effect and quick microbial adaptation to resist synthetic antibiotic has compelled researcher to find out compound from natural sources are free from side effect and resistancy. In this connection the present study has been carried out for assessment of antimicrobial activities of methanolic and aqueous extracts of leaf, stem, root and flower of Sphagneticola trilobata (L.) Pruski, against bacteria namely Pseudomonas aeruginosa (MTCC 7296), Staphylococcus aureus, (MTCC- 7443), Salmonella typhi (MTCC- 733), Mycobacterium tuberculosis (MTCC-300) and fungal organisms namely Microsporum canis (MTCC –2820), Epidermophyton floccossum (MTCC-613), Trichophyton rubrum (MTCC-296) and Aspergillus candidus (MTCC-1989). The zone of inhibition (ZOI) for the methanolic extract of leaf of S. trilobata was found 8.99±0.46mm, 16.92 ±0.58mm and 12.93±0.28mm against S. aureus, S. typhi and P. aeruginosa respectively. The ZOI for The methanolic extract of flower was found 23.79±0.27mm, 19.66 ±0.94 mm and 23.60±0.92mm against S. aureus, S. typhi and P. aeruginosa respectively. Besides, the ZOI for methanolic extract of both root and stem was found 09.19±0.34 and 08.66±0.43mm against S. aureus only. The highest zone of inhibition (23.79mm) was found in the methanolic extract of flower against S. aureus. The ZOI for methanolic and aqueous extract of leaf and methanolic extract of root was found 17.73± 0.46mm, 15.66±0.63mm and 16.19±0.33mm respectively against Epidermophyton floccossum. The ZOI for methanolic extract of leaf was found17.33±0.34mm against Trichophyton rubrum while the ZOI for aqueous extract of leaf was found 13.73±0.49 mm against Microsporum canis. The highest zone of inhibition (17.73mm) was found in the methanolic extract of leaf against Epidermophyton floccossum. Above findings may be exploited for application against respective pathogenic microorganism and modern drug formulation.